Avaliação do desempenho da segurança viária em redes urbanas de transportes com utilização de modelos de previsão de acidentes - Torres, Caio Assunção (2016)
The main road safety performance evaluation efforts commonly apply statistical modeling techniques for the frequency of traffic crashes with the use of Safety Performance Functions (SPF). This type of statistical modeling approach has been very useful when focused on isolated road entities such as intersections and road segments, mostly because it can reasonably deal with some of the stochastic problems related to the rare and random nature of crashes. Advances in data collection and spatial manipulation as well as modeling techniques have been fostering studies to support the use of SPF for safety assessment of urban networks. Given this context, this research investigates aims the use of SPF to estimate the road safety performance in urban road networks. Initially, a geographic crash database, geometric and operational attributes of the network database and vehicular flow database were consolidated using data from Fortaleza (CE). Eight SPF, for different entities of the road network, were developed applying generalized linear modeling techniques, assuming the Negative Binomial distribution for the errors. The models were applied to a sample network, in an area of city, to explore the sensitivity of the safety performance and assessing different hypothetical scenarios. Interventions in demand significantly impacted the frequency of crashes estimated by developed SPF and did not present a direct relation with the variations of the accidents. The approximately 10% increase in demand resulted in an increase of 26.8% in crashes with victims and 23.8% in total crashes. The changes made in the network supply, in general, were not statistically significant. However, when the analysis was disaggregated by zones and groups of entities, the variations became significant. The SPF estimates tended to lose their sensitivity level to the extent that reduces the analysis aggregation level due to the rare and random nature of the phenomenon. The application of the proposed methodology contributed to the improvement of practices to evaluate the road safety performance in urban transport networks. Thus, it is expected that it is possible to prevent certain negative effects generated by road accidents, reducing social and economic costs to society